Influence of tannins and mannoproteins products on the improvement of organoleptic characteristics of wines - Bilko, Marina; Gunko, Sergiy; Babich, Irina; Doboniy, Inna (My University, 2022)
The aim of the work was to establish an influence of oenological tannins and mannoproteins products on the change of the organoleptic parameters of table dry wines, made from grapes of aromatic and non-aromatic varieties. The materials of the researches were wines that had defects or faults, mainly related with changes in wine aroma and taste. Oenological tannins of various botanical origins and mannoproteins products of a company Martin Vialatte (France) were used in the researches. Wines with these additives were mixed intensively, kept during 3 days at a temperature, not exceeding 12 °C and then determined the sensory characteristics of wine. Control samples were wines without additives. The descriptive method of analysis was used to create aromatic profiles of wines. The effectiveness of tannins and mannoproteins products on the sensory characteristics of wines was established. The intensity of the descriptors that made a positive affect on the aroma and taste of the samples was increasing. If, at the beginning tones of oxidation or bitterness were felt in the wines, then after introduction of the additives, these tones decreased in intensity. A difference of the changes of aromatic characteristics of wines from two groups of grapes with different aromatics was established. The action of additives was spread on the tings of descriptors, enriching the aroma of samples from non-aromatic grape varieties together with eliminating faults of taste. The effect of the additives was light in the aromatic varieties of grape that is due to the strong aroma and expressed taste of the grapes of these varieties. The results of the researches can be used to improve the quality of white wines, and further researches should be focused on the expansion of assortments of wines from other varieties, as a result utilizing tannins and mannoprotein products.

Метою роботи було встановити вплив енологічних танінів і манопротеїнових продуктів на зміну органолептичних показників столових сухих вин, виготовлених із винограду ароматичних і неароматичних сортів. Матеріалом для досліджень були вина, які мали недоліки або недоліки, пов'язані переважно зі зміною аромату та смаку вина. У дослідженнях використовували енологічні таніни різного ботанічного походження та манопротеїнові продукти фірми Martin Vialatte (Франція). Вина з цими добавками інтенсивно змішували, витримували протягом 3 діб при температурі не вище 12 °С і потім визначали сенсорні характеристики вина. Контрольними зразками були вина без добавок. Описовий метод аналізу використовувався для створення ароматичних профілів вин. Встановлено вплив дубильних і манопротеїнових продуктів на сенсорні характеристики вин. Збільшувалася інтенсивність дескрипторів, які позитивно впливали на аромат і смак зразків. Якщо спочатку у винах відчувалися тони окислення або гіркоти, то після введення добавок інтенсивність цих тонів зменшилася. Встановлено відмінність зміни ароматичних характеристик вин з двох груп винограду з різною ароматикою. Дія добавок поширювалася на відтінки дескрипторів, збагачуючи аромат зразків неароматичних сортів винограду разом з усуваючи недоліки смаку. В ароматичних сортах винограду дія добавок була слабкою, що зумовлено сильним ароматом і вираженим смаком винограду цих сортів. Результати досліджень можуть бути використані для підвищення якості білих вин, а подальші дослідження мають бути спрямовані на розширення асортименту вин з інших сортів, в результаті використання дубильних речовин і манопротеїнових продуктів.
Keywords: кафедра біотехнології продуктів бродіння і виноробства; white wines; aroma; wine faults; mannoproteins; oenological tannins; білі вина; аромат; недоліки вина; манопротеїни; таніни енологічні